A Review of International and Russian Methodologiesto Estimate the Economic Damage Caused by Death in the Road Accidents - Karabchuk, Tatiana; Moiseeva, Anita; Soboleva, Natalia (Journal of Economic Sociology, 2015)
This article provides a review of approaches used to assess the costs of social and economic damage caused by fatalities in road accidents in Russia and other countries. The urgency of the problem is shaped by the high mortality rates of people involved in road crashes in our country compared to other countries. At the moment, absolute and relative numbers of both car accidents and fatalities in Russia are much higher than in European Union countries or in Canada and the United States. At the same time, the estimated costs of economic damage from the loss of people’s lives is much lower in Russia than in those other countries. The underestimation of human life value was discussed in details in our previous publication [Karabchuk, Nikitina, Remezkova, Soboleva 2014], where we concluded that the cost of human life in Russia is equal to the value of human life in developing countries, despite the positive trend of increases in human capital in recent years in Russia [Kapelyushnikov 2012]. The social and economic consequences of the underestimation of the value of human life can have negative effects on an individual and a country: the quality of life of Russian citizens could deteriorate and the state would lose economically active population, moreover people might feel less satisfied with their lives and less happy. Thus, it is important to develop a theoretical and methodological framework for assessing the cost of deaths caused by fatal road accidents in Russia. This article raises the question of low road safety in Russia and insufficient discussion of its consequences in the scientific literature. Comparative analysis of socio-economic damage estimates in Europe and the methods to assess them will allow us a secondary methodology of evaluating the damage caused by road accidents. That in turn will help to reduce mortality rates through the implementation of road safety programs. We review international experience and compare it with current Russian methodology; after that we summarize the results of comparative analysis and provide recommendations on how to improve methods of evaluation of socio-economic damage caused by car accidents.